Telegram: 9 reasons why we should use it? - Lehat, Mohd Lezam (Universiti Teknologi MARA, Johor, 2025)
With an ever-growing list of messaging platforms, choosing the right one can be a challenge. However, Telegram has managed to distinguish itself with a rich set of features that cater to both personal and professional users. Whether you're seeking enhanced privacy, versatile communication tools, or seamless file sharing, Telegram offers it all. Here are nine compelling reasons why you should consider using Telegram.